4 CS RULE AS A METHOD OF THE EFFICIENCY OF ADVERTISING STORYTELLING - Skorokhod, Tetiana (Collection of scientific papers «ΛΌГOΣ», 2022)
Modern advertising increasingly offers consumers to immerse themselves in a certain plot and empathize with the characters, brands communicate with their target groups also with the help of storied marketing in social media, broadcasting stories about the history of the brand, and about its team, and about its products and services. So the question of the effectiveness of storytelling, or successful stories, or stories that emotionally absorb the target audience, is relevant.